(untitled) (Research, Society and Development, 2020)
Objective: To estimate the prevalence of burnout syndrome in prehospital care nurses. Method: Exploratory research, with 105 nurses from 23 pre-hospital care bases, whose data were produced from the Maslach Burnout Inventory and an instrument elaborated by the researchers for sociodemographic characterization and recording of the physical and emotional reactions of the professionals during the visits. The data were organized in Microsoft Excel 365 spreadsheets and in the light of the conception described by Benevides-Pereira. The analysis was based on descriptive statistics and a relationship between the findings and the theoretical framework. Results: Of the 105 participants, the majority are female, aged over 30 years, married, without children, with more than 5 years of graduation, time of work in prehospital care of 5 to 6 years, weekly workload performed in pre-hospital care of up to 36 hours per week and with another employment relationship. The Maslach Burnout Inventory identified that 81 (77.14%) participants present indicative of burnout syndrome, 18 (17.14%) tendency to the syndrome and 6 (5.72%) absence of the syndrome. Physical, psychic, behavioral and defensive signs and symptoms were found, characteristic of burnout syndrome. Tiredness, low back pain, hunger, stress, lower limb pain and anger were highlighted. Conclusion: Quantitative data indicate a high prevalence of burnout syndrome in the study population. Reaffirmed through complaints that characterize reduced professional achievement, depersonalization and emotional exhaustion. It is necessary to develop programs that prioritize the physical and mental health of workers for a safe, healthy and pleasurable work practice.